Co-amorphous Solid Dispersions: Review of Underlying Theories, Recent Development and Prospective Regulatory Requirements - Abdulaziz Yasser Al Osaimi; Zeyad Khalid Aljuhani; Mansour Abdulrahman Mansour; Amjad Hashim Alsaab; Mamdouh Musaed Altalhi; Mohammed H. Elkomy; Rawan Hussain Aloufi; Majed M. Alrobaian; Ahmed M. Abdelhaleem Ali (Journal of Pharmaceutical Innovation, 2026)

Length-Weight, Length-Length, Sex Ratio, and Condition Factor of Three Loliginid Squids From the South-Eastern Arabian Sea - Tinu H.; Jeenia C.J.; Anu Thottappilly; Davood Nihal; Leena Raphael; Hashim M.; Aneesh Kumar K.V. (Thalassas: An International Journal of Marine Sciences, 2026)

Sustainable electrocoagulation treatment of tetracycline contaminated water: coupling response surface methodology with life cycle assessment - S. Mirkhalafi; M. Kiehbadroudinezhad; H. Hosseinzadeh-Bandbafha; M. Mousazadehgavan; K. S. Hashim (International Journal of Environmental Science and Technology, 2026)
Tetracycline (TC), widely used in medicine and agriculture, has emerged as a persistent micropollutant in aquatic environments, posing significant risks to human health and ecosystems due to its environmental persistence and the inefficiency of conventional treatment methods. This study aimed to develop an efficient and sustainable electrocoagulation (EC) process using aluminum electrodes to remove TC from aqueous solutions. A Box–Behnken Design (BBD) combined with Response Surface Methodology (RSM) was employed to optimize four key operational parameters, including initial pH, current intensity, inter-electrode distance, and electrolysis time. To evaluate broader sustainability, life cycle assessment (LCA) and operational cost analysis were integrated into the methodology to quantify environmental impacts and economic feasibility under optimized conditions. The developed quadratic model showed good agreement between predicted and experimental results (R 2 = 0.887), confirming the reliability of the optimization approach. TC removal efficiencies reached up to 100% under optimized operating conditions. LCA results indicated that neutral pH and low current minimized environmental burdens, with the lowest weighted total damage (~ 0.3 mPt/FU), while intensive conditions significantly increased impacts. Overall, integrating EC with RSM, LCA, and cost analysis provides a comprehensive framework for designing technically effective, environmentally sustainable, and economically feasible treatment of antibiotic-contaminated waters.

Remote sensing for Antarctic geological mapping: Evidence, validation challenges and future directions - Khurram Riaz; Amin Beiranvand Pour; Aidy M. Muslim; Saima Khurram; Adel Shirazy; Aref Shirazi; Jabar Habashi; Basem Zoheir; Mazlan Hashim; Sareh Sadigh (Remote Sensing Applications: Society and Environment, 2026)

Comparative otolith morphology and ontogenetic variation in deep-sea demersal scorpaenoid fishes from the northern Indian Ocean - Davood Nihal; K. V. Aneesh Kumar; Víctor M. Tuset; Antoni Lombarte; Hashim Manjebrayakath (Zoomorphology, 2026)

PROMETHEUS clinical trial protocol: tailoring healthy ageing with lifestyle and nutraceuticals - Ajla Hodzic Kuerec; Lihuan Guan; Weilan Wang; Duarte Barros; Wejdan M. Alenezi; Jozo Grgic; Vanessa K. Wazny; Jordi Morwani-Mangnani; Mazzarine Dotou; Dingding Zhang; Tong Chen; Jiaqiu Wang; et al. (GeroScience, 2026)
The d emographic shift toward an older population is accelerating the prevalence of age-related diseases. Precision geromedicine represents a paradigm shift in targeting the biological processes of ageing to optimise health and healthspan, which likely requires multimodal tailored interventions. PROMETHEUS, as part of the XPRIZE healthspan semi-finalist competition, is an 8-week feasibility and exploratory study including 20 middle-aged-to-older participants who received a multimodal intervention comprising fundamental and augmented interventions. The fundamental interventions include sleep and dietary recommendations; supplementation with whey protein, creatine, and fucoidan; supervised exercise with an exergaming component (dual-task cognitive-physical training); motivational interviewing; and cognitive behavioural therapy. The augmented intervention is further personalised based on predefined gerotypes, reflecting individual ageing patterns beyond chronological age. At baseline, urolithin A, nicotinamide mononucleotide, and/or multivitamin-multimineral were prescribed to participants based on their muscle mass, VO 2 peak, and cognitive performance. At mid-intervention, interventions were adjusted based on individual response, including dose escalation and/or the addition of ergothioneine for inadequate improvement in cognition. Primary outcomes include measures of muscle strength and mass, immune function and cognitive performance, and feasibility indicators such as adherence and trial completion. Secondary outcomes include assessments of other biological, clinical, and digital biomarkers of ageing, as well as qualitative indicators of motivation and personal values. This study is aimed at investigating the recruitment feasibility, safety, adherence, and exploratory outcome trajectories of a multimodal, personalised precision geromedicine intervention protocol based on individual participant’s baseline characteristics and interim responses. These findings will also inform the design of a subsequent 12-month, randomised controlled trial evaluating personalised lifestyle and nutraceutical strategies with the potential to incorporate repurposed pharmacological agents to optimise age-related health outcomes.

Synthesis, structural characterization, biological activity of trace metal complexes with a 2-aminobenzothiazole-derived schiff base: Experimental and docking studies - Doaa Neamah Mohsen; K.M. Tawfiq; Ismaeel Y. Majeed; Hany M. Abd El-Lateef; Mayada Sabri; Rasha Ahmed Hashim; Amer J. Jarad; Abaas Obaid Hussein; Antar A. Abdelhamid; Manal M. Alzahrani; Mohamed Abdelbaset; Ahmed A. Elhenawy (Journal of Trace Elements in Medicine and Biology, 2026)

Cell-based and computational toxicity profiling of thiourea and imine derivatives in Acanthamoeba sp. as environmental bioindicators for potential optoelectronic applications - Thivyan Manisekaran; Wan M. Khairul; Nur Amirah Nabilah Mohd Rashid; Fariq Zulfaqar Musa; Syed Ahmad Tajudin Tuan Johari; Siti Aisyah Razali; Fatimah Hashim; Mas Mohammed; Rafizah Rahamathullah; Amira Nabiha Najwa Syahrul Fahmy (Chemosphere, 2026)

Monthly and annual temporal-spatial analysis of the atmospheric clearness index over Iraq - Yasmin Q. Tawfeeq; Luma M. Al-Saadi; Shiemaa A. Hashim; Monim H. Al-Jiboori (Environmental Monitoring and Assessment, 2026)

Fabrication of ginger extract–loaded PAN nanofiber mats as a non‑contact natural antioxidant system for preserving soybean oil - Shamous M. Ibrahim; Ayat F. Hashim; Ayman El Said; Tamer Hamouda (Food Packaging and Shelf Life, 2026)

Oral delivery of an ustekinumab biosimilar with bioavailability comparable to subcutaneous administration in healthy human participants - Joshua T. Myers; Alyson Yamaguchi; Kyle Horlen; Leonard C. Fung; April Toledo Vo; Deepa Mohan; Mary Hoopes; Mir Imran; Jacques Van Dam; Ofer M. Gonen; Mir A. Hashim; Arvinder K. Dhalla; et al. (European Journal of Clinical Pharmacology, 2026)

Actinomycetes in the spotlight: biodiversity and their role in bioremediation - Hagar S. Hashim; Mazen M. Zayan; Ahlam A. Mohamed; Hend Ismail Abd El rahman Abulila (World Journal of Microbiology and Biotechnology, 2026)

Vulnerability of tropical fish communities across depth in the central Indian Ocean - Paris V. Stefanoudis; Nina M. de Villiers; Mariyam Shidha Afzal; Hana Amir; Farah Amjad; Aminath Shaha Hashim; Ahmed Riyaz Jauharee; Ryan Palmer; Alex D. Rogers; Mohamed Shimal; Shafiya Naeem; Mohamed Ahusan; et al. (Conservation Biology, 2025)
Coral reefs and their fish communities below scuba diving depth (>30 m), in mesophotic coral ecosystems (MCEs) (∼30–150 m), in rariphotic (150–300 m), and in upper bathyal waters (300–500 m) are often underexplored, especially in the Indian Ocean. The paucity of data, including on the biodiversity, ecology, and vulnerability of these habitats and the communities they support, leads to their omission from most conservation and management decisions and practices. We investigated for the first time the structure and diversity (taxonomic and functional) of demersal fish communities from the central and southern atolls of the Maldives, spanning a wide bathymetric gradient of 2–500 m to better understand whether and how their vulnerability changes across depth. Abundance and biomass data from transect surveys of demersal fishes were combined with species’ trait data representing life histories to estimate a series of taxonomic‐based and functional‐based diversity metrics. Distinct fish communities occurred across the different surveyed depths, highlighting the unique biological characteristics of MCEs and deep‐sea coral habitats in the Indian Ocean. Taxonomic and functional diversity decreased as depth increased, and there was little overlap between species’ life‐history strategies. This suggests deep habitats are more vulnerable than shallow habitats to disturbance events given low levels of trait redundancy that buffer species’ trait loss. Moreover, many fishes living in MCE and deep‐sea habitats were among the most functionally unique species (e.g., sharks and rays) and all were threatened with extinction. Given the suite of pressures MCEs and deep‐sea habitats are subjected to (fishing, thermal stress, pollution), their vulnerability to disturbance, and the species of conservation concern they support, we suggest they should be considered as priorities in ongoing and future conservation and marine spatial planning initiatives in the region and globally.

Esterification of Acidic Crude Palm Oil Using Trickle Bed Reactor Packed With Supported p-Toluenesulfonic Acid Monohydrate-Based Deep Eutectic Solvent - Adeeb Hayyan; Inas M. AlNashef; Sharifah Shahira Syed Putra; Mohd Ali Hashim; Yousef Mohammed Alanazi; Jehad Saleh; Bhaskar Sen Gupta; Andrew T. H. Yeow; Low Wei Seng; M. K. Kow (BioEnergy Research, 2025)

Recent developments in NOx capture and conversion using nano-structured materials: A comprehensive review - Rida M. Bin Hashim; Mahmoud N. Almakhadmeh; Sagheer A. Onaizi (Journal of Environmental Chemical Engineering, 2025)

Revealing critical mineralogical insights in extreme environments using deep learning technique on hyperspectral PRISMA satellite imagery: Dry Valleys, South Victoria Land, Antarctica - Jabar Habashi; Amin Beiranvand Pour; Aidy M. Muslim; Ali Moradi Afrapoli; Jong Kuk Hong; Yongcheol Park; Alireza Almasi; Laura Crispini; Mazlan Hashim; Milad Bagheri (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Therapeutic innovations: targeting ROS production in AML with natural and synthetic compounds - Mohammed Hashim Mohammed; Raed Fanoukh Aboqader Al-Aouadi; Subasini Uthirapathy; Gaurav Sanghvi; Rekha M M; Resan Shakir Abdulamer; G. V. Siva Prasad; Mayank Kundlas; Fayzulla Khamraev; Muhammad Ikram Ullah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Finite element modelling of the mechanical behavior of papaya fruit under compression - Ademola M. Aina; Hazreen H. Harith; Norhashila Hashim; Mohamad Firdza Mohamad Shukery (Postharvest Biology and Technology, 2025)

Machine learning, network pharmacology, and molecular dynamics reveal potent cyclopeptide inhibitors against dengue virus proteins - Mohammed A. Imam; Thamir A. Alandijany; Hashim R. Felemban; Roba M. Attar; Arwa A. Faizo; Hattan S. Gattan; Vivek Dhar Dwivedi; Esam I. Azhar (Molecular Diversity, 2025)

Three-dimensional reservoir modeling of the pliocene reservoir based on seismic data advances for new prospect assessment - Nader H. Elgendy; Mohamed Reda; Mohamed M. Elmashaly; Abdelmoneam Raef; Mansour H. Al-Hashim; Moataz Kh. Barakat (Marine Georesources & Geotechnology, 2025)

An environmental friendly phenylphosphonate functionalised graphene oxide/HDPE composite towards flame retardant: Experimental, thermal and cytotoxicity evaluation - Chiong Hwee Hii; Wan M. Khairul; Alyza A. Azmi; R.M. Kasmani; Fatimah Hashim; Rafizah Rahamathullah; Syed Ahmad Tajudin Tuan Johari; Farhanini Yusoff; Norazlan Mohmad Misnan (Journal of Environmental Chemical Engineering, 2025)

Numerical Models for Establishing Relationships Between Otolith Morphometrics and Fish Size in Deep-Sea Scorpaenoid and Dactylopterid Fishes - Davood Nihal; Aneesh Kumar K. V.; Purbali Saha; M. P. Rajeeshkumar; Hashim Manjebrayakath (Thalassas: An International Journal of Marine Sciences, 2025)

Chitosan-coated liposomes of pomegranate-peel phenolic extract: Maximizing the bioaccessibility and antimicrobial activity in probiotic goat yoghurt - Malikakhon Kurbonova; Marwa M. El-Said; Samah M.S. EL-Shafei; Victoria llina; Hoda S. El-Sayed; Wael M. Elmessery; Mahmood A. Hashim; Tamer M. El-Messery (Journal of Stored Products Research, 2025)

Fast visual detection of sunflower oil thermal oxidation using Polyacrylonitrile/Congo red nanofiber mats - Ayat F. Hashim; Ghada A. Abo-Elwafa; Shamous M. Ibrahim; Tamer Hamouda (Food Chemistry, 2025)

Coconut husk ash and polyethersulfone mixed matrix membrane analysis for textile wastewater and humic acid filtration process - M. S. A. Rahman; F. M. Zuki; M. U. M. Junaidi; N. Kasim; N. A. Hashim (International Journal of Environmental Science and Technology, 2025)

Paleobiodiversity, Paleobiogeography, and Paleoenvironments of the Middle–Upper Eocene Benthic Foraminifera in the Fayum Area, Western Desert, Egypt - Mostafa M. Sayed; Petra Heinz; Ibrahim M. Abd El-Gaied; Ramadan M. El-Kahawy; Dina M. Sayed; Yasser F. Salama; Mansour H. Al-Hashim; Michael Wagreich (Journal of Marine Science and Engineering, 2025)
The middle–upper Eocene successions of northwest Fayum, Egypt, provide a crucial archive for reconstructing paleoenvironmental conditions and paleobiogeographical patterns of the southern Tethys realm. Stratigraphically, the investigated section is subdivided into three rock units: the Gehannam Formation (Bartonian-Priabonian), the Birket Qarun Formation, and the Qasr El Sagha Formation (Priabonian). A total of 101 benthic foraminiferal taxa, representing 31 genera, 23 families, 13 superfamilies, and four suborders, were identified. The middle–late Eocene age is primarily determined by the co-occurrence of index spinose planktonic foraminifera (Acarinina spp., Morozovelloides spp., and Globigerinatheka semiinvoluta) and benthic foraminiferal assemblages, further supported by the presence of the nannofossil marker Chiasmolithus oamaruensis. Four local benthic biozones are identified and correlated with coeval zones in nearby areas. Quantitative analyses of benthic foraminiferal individuals, diversity indices, ecological parameters, and the benthic foraminiferal oxygen index (BFOI) reveal distinct environmental shifts. The rock unit occupied by the late middle Eocene assemblages is diversified and dominated by calcareous infaunal taxa (e.g., Bolivina spp., Fursenkoina spp., and Nonionella spp.), indicative of low-oxygen outer neritic conditions associated with elevated organic influx. In contrast, the late Eocene Birket Qarun and Qasr El Sagha showed an increase in epifaunal forms and reduced diversity, suggesting a transition to dysoxic-oxic conditions. Paleobiogeographical analysis indicates a strong affinity with the Tethyan realm, with potential faunal exchange through the Trans-Saharan Seaway. These findings enhance our understanding of Paleogene marine connections between the Tethyan and Indo-Pacific realms, contributing to broader discussions on Eocene paleobiogeography and depositional dynamics in North Africa.

Development of radionuclide inventory and fission product release calculation model and its application to HTR-PM - Sohail Ahmad Raza; Liangzhi Cao; Yongping Wang; Yuxuan Wu; Haoyong Li; M. Hashim (Annals of Nuclear Energy, 2025)

Foraminiferal biostratigraphy and depositional environment of the late Albian–Cenomanian Al Hilal formation in northeastern Libya - Ibrahim M. Abd El-Gaied; Yasser F. Salama; Mansour H. Al-Hashim; Michael M. Grammer; Sayed M. Abd El-Aziz (Carbonates and Evaporites, 2025)

D-Glucosamine is a Potential Urease Inhibitor from Middle Eastern Medicinal Plants for Combatting Helicobacter Pylori Infections; a Molecular Docking and Simulation Approach - Mohammed Baqur S. Al-Shuhaib; Hayder O. Hashim; Jafar M. B. Al-Shuhaib (Biochemical Genetics, 2025)

Levulinic acid-based deep eutectic solvent and n-heptane for efficient oil extraction process from rubber seed - Mohammed Abobakr Al-Maari; Hanee F. Hizaddin; Adeeb Hayyan; Khalid M. Abed; Wan Jefrey Basirun; Yousef Mohammed Alanazi; Jehad Saleh; Mohd Ali Hashim; Bhaskar Sen Gupta (Food and Bioproducts Processing, 2025)

Synthesize of an Azo Compound: Investigation its Optical Nonlinear Properties and DFT Study - Sadiq M. H. Ismael; Numan S. Hashim; F. A. Al-Saymari; H. A. Sultan; Qusay M. A. Hassan; Kawkab Ali Hussein; C. A. Emshary; Hanadi M. Jarallah (Journal of Fluorescence, 2024)

Length-Weight Relationships of Eight Fish Species Collected as Bycatch from Deep-Sea Shrimp Trawls Operated in the Arabian Sea - Davood Nihal; K. V. Aneesh Kumar; Purbali Saha; M. P. Rajeeshkumar; Hashim Manjebrayakath (Thalassas: An International Journal of Marine Sciences, 2024)

Metabolomics analysis of Citrus medica var. sarcodactylis (Siebold ex Hoola van Nooten) Swingle and Limonia acidissima Linn. fruits and leaves in perspective to their antimicrobial potential - Abeer M. El Sayed; Eman A. W. El-Abd; Fatma A. Hashim; Mohamed A. Farid; Hoda M. A. H. Shata; Seham S. El Hawary (Natural Product Research, 2024)

Assessment on functionalized conjugated acetylide and its designated acetylide-imine moieties towards Acanthamoeba sp.: An in vitro bioindicator study - Thivyan Manisekaran; Wan M. Khairul; Yinn Dorng Foong; Syed Ahmad Tajudin Tuan Johari; Fatimah Hashim; Rafizah Rahamathullah; Mas Mohammed (Chemosphere, 2024)

Emulsion liquid membrane pertraction of soap from crude biodiesel using activated carbon and glycol based deep eutectic solvents - Khalid M. Abed; Adeeb Hayyan; Hanee F. Hizaddin; Mohd Ali Hashim; Yee-Sern Ng; Wan Jefrey Basirun; Yatimah Alias; Muhammad Zulhaziman Mat Salleh (Journal of Cleaner Production, 2024)

An updated checklist of Myctophids of Western Indian Ocean with 6 new records - K.M. Meera; V.N. Sanjeevan; R. Raghu Prakash; M. Hashim (Regional Studies in Marine Science, 2024)

Exploring the macrominerals and heavy metals profile of deep-sea fishes: A pioneering study on trawl bycatch and discards in the Arabian Sea - N. Davood; M. Vidya; N. Abhirami; K.V. Vishnu; K.V. Aneesh Kumar; M.P. Rajeeshkumar; M. Hashim (Marine Pollution Bulletin, 2024)

Effectiveness of ammonium-based deep eutectic solvents in extracting polyphenol from Chlorella vulgaris - Mohamad Hamdi Zainal-Abidin; Jia Jia Eng; Khairunnisa’ Khairuzi; Sonny Kristianto; Wan M. Asyraf Wan Mahmood; Abdo Mohammed Al-Fakih; Juan Matmin; Roswanira Abdul Wahab; Faizuan Abdullah; Mohd Fuad Mohamad; Siti Ernieyanti Hashim; Hwee Li Teo; et al. (Algal Research, 2024)

New Record of Plain Helmet Gurnard fish Dactyloptena tiltoni (Teleostei: Dactylopteriformes) from the Northern Indian Ocean - Davood Nihal; M. P. Rajeeshkumar; Purbali Saha; K. V. Aneesh Kumar; Hashim Manjebrayakath (Thalassas: An International Journal of Marine Sciences, 2024)

Dolomite as a potential adsorbent in water treatment: pH, turbidity and Pb (II) removal studies - N. A. Jamil; M. F. A. Patah; M. U. M. Junaidi; B. M. Jan; F. M. Zuki; C. K. Tan; M. I. M. Nor; N. H. Hashim (International Journal of Environmental Science and Technology, 2024)

Microplastic assessment in the benthic ecosystem of Tokyo Bay: Sediment, water, and macrobenthic perspectives - Said M. Hashim; Md. Jahangir Alam; Zijiang Yang; Hisayuki Arakawa (Regional Studies in Marine Science, 2024)

Immune Cell Profiling in the Ovarian Stroma of a Viviparous Fish during the Breeding Season: A Histological and Immunohistochemical Investigation - Ramy K. A. Sayed; Doaa M. Mokhtar; Madeha Ahmed Hashim; Ahmed S. Aly; Giacomo Zaccone; Marco Albano; Alessio Alesci; Nada Abdellah (Fishes, 2023)
The molly fish is a member of viviparous teleosts that are characterized by the fusion of the right and left ovaries during their early embryonic development. This fusion results in a singular and saccular ovary, where the germinal epithelium lines the internal lumen. The present study aimed to identify the immune cells in the ovarian stroma of Molly fish during the breeding season using histological and immunohistochemical analysis. Histological examination of the ovaries displayed oocytes at all different stages of development and degeneration. The ovocoel, a lymph-filled space, remains in the center of the ovary and branches posteriorly, creating the lumen of the gonoduct. The ovarian wall is composed of three layers: the mesothelium, tunica albuginea, and germinal epithelium. The developing ova were held together by the stroma, which consisted of vascular collagenous connective tissue clustered with immune cells. Immunohistochemical analysis revealed the presence of clusters of macrophages expressing APG5, IL-1β, TGF-β, S100, NF-κB, CD68, Iba-1, and Ach. Monocytes demonstrated positive immunoreactivity for both APG5 and IL-1β, whereas dendritic cells expressed only APG5. Furthermore, rodlet cells exhibited immunoreactivity for S100 protein, IL-1β, NF-κB, CD68, Nrf2, Ach, myostatin, SOX9, and Iba-1. In contrast, stem cells displayed immunoreactivity for Nrf2, myostatin, and SOX9. In conclusion, the ovarian stroma of Molly fish demonstrated a notable presence of immune cells, indicating their active involvement in immune reactions.

In vitro–in vivo assessments of apocynin-hybrid nanoparticle-based gel as an effective nanophytomedicine for treatment of rheumatoid arthritis - Reham Mokhtar Aman; Randa Ahmed Zaghloul; Wael M. Elsaed; Irhan Ibrahim Abu Hashim (Drug Delivery and Translational Research, 2023)
Apocynin (APO), a well-known bioactive plant-based phenolic phytochemical with renowned anti-inflammatory and antioxidant pharmacological activities, has recently emerged as a specific nicotinamide adenine dinucleotide phosphate-oxidase (NADPH) oxidase inhibitor. As far as we know, no information has been issued yet regarding its topical application as a nanostructured-based delivery system. Herein, APO-loaded Compritol ® 888 ATO (lipid)/chitosan (polymer) hybrid nanoparticles (APO-loaded CPT/CS hybrid NPs) were successfully developed, characterized, and optimized, adopting a fully randomized design (3 2 ) with two independent active parameters (IAPs), namely, CPT amount (X A ) and Pluronic ® F-68 (PF-68) concentration (X B ), at three levels. Further in vitro–ex vivo investigation of the optimized formulation was performed before its incorporation into a gel base matrix to prolong its residence time with consequent therapeutic efficacy enhancement. Subsequently, scrupulous ex vivo–in vivo evaluations of APO-hybrid NPs-based gel (containing the optimized formulation) to scout out its momentous activity as a topical nanostructured system for beneficial remedy of rheumatoid arthritis (RA) were performed. Imperatively, the results support an anticipated effectual therapeutic activity of the APO-hybrid NPs-based gel formulation against Complete Freund’s Adjuvant-induced rheumatoid arthritis (CFA-induced RA) in rats. In conclusion, APO-hybrid NPs-based gel could be considered a promising topical nanostructured system to break new ground for phytopharmaceutical medical involvement in inflammatory-dependent ailments. Graphical Abstract

Biochar-layered double hydroxide composites for the adsorption of tetracycline from water: synthesis, process modeling, and mechanism - Mukarram Zubair; Mohammad Saood Manzar; Amjad El-Qanni; Hajira Haroon; Hissah A. Alqahtani; Maryam Al-Ejji; Nuhu Dalhat Mu’azu; Jwaher M. AlGhamdi; Shamsuddeen A. Haladu; Dana Al-Hashim; Syed Z. Ahmed (Environmental Science and Pollution Research, 2023)

The moderating role of CEO power on the relationship between environmental, social and governance disclosure and financial performance in emerging market - Waleed M. Al-ahdal; Najib H. S. Farhan; Rachana Vishwakarma; Hafiza Aishah Hashim (Environmental Science and Pollution Research, 2023)

Aquatic toxicity of hydroquinone and catechol following metal oxide treatment to Ceriodaphnia dubia and Pimephales promelas - Mohd Kotaiba Abugazleh; Hashim M. Ali; Jae A. Chester; Ahed M. Al-Fa’ouri; Jennifer L. Bouldin (Ecotoxicology, 2023)

Influence of Geometric Parameters on the Charging process of PCM in Semi-circular thermal storages for energy management - Mohsen Izadi; Arslan Saleem; Hashim M. Alshehri; Tehmina Ambreen; Amir Karimdoost Yasuri (Environmental Science and Pollution Research, 2023)

Artificial reef structures and coral transplantation as potential tools for enhancing locally-managed inshore reefs: a case study from Wasini Island, Kenya - Jelvas M. Mwaura; Dishon Murage; Juliet F. Karisa; Levy M. Otwoma; Hashim O. Said (Western Indian Ocean Journal of Marine Science, 2023)
Many severely degraded reefs in the western Indian Ocean region show no signs of natural recovery and have remained for decades as barren, unconsolidated coral rubble fields with depleted commercially important fish groups. Consequently, several restoration techniques have been designed and developed to mitigate the localized impacts on coral reefs. Evaluating the efficacy of combined use of artificial reef structures and coral transplantation in enhancing habitat and recovery of key functions in severely degraded reefs is key to improved conservation of coral reefs. In this study, the survivorship rate of corals transplanted on reef structures is assessed, and changes in coral and fish abundance on artificial reef units and nearby natural reefs over time are compared. Coral cover on artificial reef structures increased from a mean of 17 % one year after initial attachment of fragments to 41 % after two years, with Acropora corals providing the highest cover. The artificial reef structures were also rapidly colonized by reef fish, with fish densities of 18±13 indiv./100 m2 showing an increase of about three fold higher than on natural reefs after two years. Greater numbers of commercially important fish groups (e.g., Lutjanids and Acanthurids) were observed on artificial reefs while natural reefs harboured more small sized fish (Pomacentrids and Labrids). These findings provide insights for artificial reef projects that are capable of restoring the regenerative capacity of the human-induced coral rubble beds.

Ketoprofen and aspirin removal by laccase immobilized on date stones - Osamah J. Al-sareji; Mónika Meiczinger; Jasim M. Salman; Raed A. Al-Juboori; Khalid S. Hashim; Viola Somogyi; Miklós Jakab (Chemosphere, 2023)

Smart films of carbohydrate-based/sunflower wax/purple Chinese cabbage anthocyanins: A biomarker of chicken freshness - Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Li Lui; Junjun Zhang; Xiaodong Zhai; Amer Ali Mahdi; Nosyba A. Ibrahim; Gustav Komla Mahunu; Mahmoud M. Hassan; Zou Xiaobo; Shi Jiyong (Food Chemistry, 2023)

Seroprevalence of camel brucellosis in Qatar - Hashim Alhussain; Susu M. Zughaier; Ahmed Gawish; Mahmoud H. Mahmoud; Hadi M. Yassine; Asmaa Al Thani; Tahra El- Obied; Abdulaziz M. Al-Zeyara; Nahla O. Eltai (Tropical Animal Health and Production, 2022)
Brucellosis is a significant zoonotic disease and one of the most common neglected diseases worldwide. It can infect a wide range of domestic and wild animal species. Infected animals are usually culled, causing substantial economic losses to animal owners and the country’s economy in general. The disease is endemic among cattle, sheep, and goats in many countries around the Middle East and prevalent in most Gulf Cooperation Council countries, comprising a significant public health risk in the region. This study investigated the seroprevalence of brucellosis among camels in Qatar. Two hundred and forty-eight samples were collected from dromedary camels from 28 farms across the entire country. Each sample was tested for Brucella antibodies with both Rose Bengal and competitive enzyme-linked immunosorbent assay. Only samples that tested positive by both tests were considered seropositive for brucellosis. The overall prevalence was (20.6%, 95% CI, 15.7–26.1). The association between sex and seropositivity was slightly significant ( Χ 2 = 4.32, P = 0.04), with higher seroprevalence in females. Camels below breeding age (i.e., < 4 years old) showed decreased seropositivity (3.4%, 95% CI, 0.1–17.8), compared to (22.8%, 95% CI, 17.4–29.0) seropositivity in camels ≥ 4 years of age, with a significant association between age groups and seropositivity ( P = 0.02). Our results indicate that the seroprevalence of brucellosis in Qatar’s camels is alarming, mandating more efforts to control the disease. The findings of this study will aid in selecting better effective measures to control camel brucellosis in Qatar. Further studies need to be conducted on Brucella infection among camels to determine the predisposing risk factors and the steps that should be followed to control brucellosis.

Association of OLR1 gene polymorphism with live body weight and body morphometric traits in Awassi ewes: short communication - Majeed H. Ajafar; Tahreer M. AL-Thuwaini; Hashim H. Dakhel (Molecular Biology Reports, 2022)

Inferring ecological strategies of Psenopsis spp. (Teleostei: Centrolophidae) inhabiting Indian waters from morphological features - K. V. Aneesh Kumar; M. P. Rajeeshkumar; M. Hashim; K. P. Deepa; J. L. Otero-Ferrer; N. Saravanane; Sujitha Thomas; K. K. Bineesh; V. M. Tuset (Marine Biology Research, 2022)

Phenylpropanoid-conjugated iridoid glucosides from leaves of Morinda morindoides - Yasinjan Hashim; Kazufumi Toume; Shusaku Mizukami; Toshinori Kitami; Mayumi Taniguchi; Awet Alem Teklemichael; Yuki Tayama; Nguyen Tien Huy; José Nzunzu Lami; Joseph M. Bodi; Kenji Hirayama; Katsuko Komatsu (Journal of Natural Medicines, 2022)

Environmental monitoring of anthropogenic impacts and climate change: a case study from the national network of roads in Egypt - AlBaraa ElSaied; Haitham Farouk; Mohamed Elhady; Zeinab D. Almarid; Ahmed M. Hashim (Environmental Science and Pollution Research, 2021)

New Distributional Record of Peristedion liorhynchus (Scorpaeniformes: Peristediidae) From Central Indian Ocean - Rajeeshkumar M. P; Rajeev R; Hashim M; Saravanane N (Thalassas: An International Journal of Marine Sciences, 2021)

Phenylpropanoid conjugated iridoids with anti-malarial activity from the leaves of Morinda morindoides - Yasinjan Hashim; Kazufumi Toume; Shusaku Mizukami; Yue-Wei Ge; Mayumi Taniguchi; Awet Alem Teklemichael; Nguyen Tien Huy; Joseph M. Bodi; Kenji Hirayama; Katsuko Komatsu (Journal of Natural Medicines, 2021)

Ameliorative effect of N-acetylcysteine against glyphosate-induced hepatotoxicity in adult male albino rats: histopathological, biochemical, and molecular studies - Asmaa R. Hashim; Dina W. Bashir; Noha A. E. Yasin; Mona K. Galal; El-Gharbawy S. M. (Environmental Science and Pollution Research, 2021)

Rapid and optimized protocol for efficient PCR-SSCP genotyping for wide ranges of species - Milad A. Badi; Mohammed Baqur S. Al-Shuhaib; Thamer R. S. Aljubouri; Tahreer M. Al-Thuwaini; Halla H. Dawud; Tamadhur H. Hussein; Amir T. Al-Nafii; Dhafer Abdulmalek; Mohammed K. A. Altamemi; Israa A. Fadhil; Ali H. Albakri; Hayder O. Hashim; et al. (Biologia, 2021)

Risk assessment of horizontal curves using reliability analysis based on Google traffic data - Eman K. Ali; Ibrahim H. Hashim; Sayed A. Shwaly; Zaki M. Zidan; Sherif M. El-Badawy (Innovative Infrastructure Solutions, 2021)

Sedimentomorphic geodiversity in response to depositional environments: remote sensing application along the coastal plain between Ummlujj and Al-Wajh, Red Sea, Saudi Arabia - Mansour H. Al-Hashim; Hesham M. El-Asmar; Mohamed E. Hereher; Fahad Alshehri (Arabian Journal of Geosciences, 2021)

Improving the geotechnical properties of high expansive clay using limestone powder - Hawkar Hashim Ibrahim; Younis M. Alshkane; Yousif Ismael Mawlood; Krikar M. Gharrib Noori; Ahmed Mohammed Hasan (Innovative Infrastructure Solutions, 2020)

Environmental monitoring and prediction of land use and land cover spatio-temporal changes: a case study from El-Omayed Biosphere Reserve, Egypt - Ahmed M. Hashim; Amr Elkelish; Haifa A. Alhaithloul; Shaimaa M. El-hadidy; Haitham Farouk (Environmental Science and Pollution Research, 2020)

Estimation of Total Dissolved Solids in Water Bodies by Spectral Indices Case Study: Shatt al-Arab River - Ali A. A. Maliki; Ali Chabuk; Maitham A. Sultan; Bassim M. Hashim; Hussain M. Hussain; Nadhir Al-Ansari (Water, Air, & Soil Pollution, 2020)
In recent years, the problem of rising salinity levels in the Shatt al-Arab river in southern Iraq has been repeated, which has directly affected the living and health situation and the agricultural activity of these areas. Six sampling stations were selected along Shatt al-Arab to estimate the concentration of total dissolved solids (TDS) in the river; these stations included the following: Qurna, Labani, City Centre, Kateban, Corniche, and Sihan. In addition, three Landsat-8 satellite images which were taken at the same time as collected samples also used for detecting the salinity in the river. After processing of atmospheric correction and inserted remote sensing indices, the reflectance of water extracted from satellite images was used to express the spectral characteristics of different TDS concentrations. Correlation and regression were used to obtain accurate models for detecting the salinity depending on the spectral reflectance of Landsat 8 operational land image OLI. The results presented Pearson correlation ( r ) value of 0.70, 0.97, and 0.71, and correlation coefficient ( R 2 ) of 0.56, 0.94, and 0.85 between field data with spectral data of salinity index 2 (SI-2) derived from the green and blue bands of Landsat obtained in 2015, 2017, and 2018 respectively. In conclusion, remote sensing and GIS technologies coupled with spectral modeling are useful tools for providing a solution of future water resources planning and management, and also offer great undertaking as a means to improve knowledge of water quality and support water decision making.

Longer mosquito control using a sodium alginate–chitosan nanocarrier for cinnamaldehyde in larvicide formulations - S. T. S. Wong; A. Kamari; A. M. Jaafar; M. Z. Hussein; H. Othman; H. Abdullah; N. Yusof; N. Hashim (Environmental Chemistry Letters, 2020)

New Geographical Record of Chaunax penicillatus McCulloch, 1915 (Chaunacoidei: Chaunacidae) from the Eastern Indian Ocean - M. P. Rajeeshkumar; K. K. Bineesh; M. Hashim; Sherine Sonia Cubelio; M. Sudhakar (Thalassas: An International Journal of Marine Sciences, 2020)

Geoarcheomorphosites under Strong Urbanization Pressure at the Tineh Plain, NE of the Nile Delta, Egypt - Maysa M. N. Taha; Mansour H. Al-Hashim; Hesham M. El-Asmar (Geoheritage, 2020)

Near reef abundance and on–offshore distribution of tuna larvae around Minicoy Island in Lakshadweep Sea, India - K. V. Aneesh Kumar; K. P. Deepa; M. M. Muhammed Rafeeq; G. Sree Renjima; Hashim Manjebrayakath; B. R. Smitha; N. Saravanane; M. P. Prabhakaran; V. N. Sanjeevan; M. Sudhakar (Marine Biology Research, 2020)

A Method for Predicting Long-Term Municipal Water Demands Under Climate Change - Salah L. Zubaidi; Sandra Ortega-Martorell; Patryk Kot; Rafid M. Alkhaddar; Mawada Abdellatif; Sadik K. Gharghan; Maytham S. Ahmed; Khalid Hashim (Water Resources Management, 2020)

Environmental assessment of heavy metal pollutants in soils and water from Ortum, Kenya - F. O. Wanjala; N. O. Hashim; D. Otwoma; C. Nyambura; J. Kebwaro; M. Ndege; S. Bartilol (Environmental Monitoring and Assessment, 2020)

Anxiolytic and anticonvulsant activity followed by molecular docking study of ceramides from the Red Sea sponge Negombata sp - Nermeen A. Eltahawy; Amany K. Ibrahim; Mohamed S. Gomaa; Sawsan A. Zaitone; Mohamed M. Radwan; Hashim A. Hassanean; Mahmoud A. ElSohly; Safwat A. Ahmed (Medicinal Chemistry Research, 2019)

Incorporation of Electrochemically Exfoliated Graphene Oxide and TiO2 into Polyvinylidene Fluoride-Based Nanofiltration Membrane for Dye Rejection - A. B. Suriani; Muqoyyanah; A. Mohamed; M. H. D. Othman; R. Rohani; I. I. Yusoff; M. H. Mamat; N. Hashim; M. N. Azlan; M. K. Ahmad; P. Marwoto; Sulhadi; et al. (Water, Air, & Soil Pollution, 2019)

Assessment of the impact of coastal reclamation activities on seagrass meadows in Sungai Pulai estuary, Malaysia, using Landsat data (1994–2017) - Mohammad S. Hossain; Mazlan Hashim; Japar S. Bujang; Muta H. Zakaria; Aidy M. Muslim (International Journal of Remote Sensing, 2019)

A Stranding Record of Dwarf Sperm Whale Kogia sima in Lakshadweep Archipelago, India and its Genetic Analogy by Molecular Phylogeny - K. V. Aneesh Kumar; Sibi T. Baby; K. V. Dhaneesh; Hashim Manjebrayakath; N. Saravanane; M. Sudhakar (Thalassas: An International Journal of Marine Sciences, 2019)

Sero-prevalence of peste des petits ruminants virus antibodies in sheep and goats from the Sudan, 2016–2017 - Nussieba A. Osman; Hashim M. A. Ibrahim; Alwia A. Osman; Rihab M. Alnour; Omiema A. Gamal Eldin (VirusDisease, 2018)

Eco-friendly smart hydrogels for soil conditioning and sustain release fertilizer - J. Pushpamalar; S. J. Langford; M. B. Ahmad; Y. Y. Lim; K. Hashim (International Journal of Environmental Science and Technology, 2018)

Aberrant Expression of Some Circulating miRNAs in Childhood Acute Lymphoblastic Leukemia - Menha Swellam; Maha Hashim; Magda Sayed Mahmoud; Amal Ramadan; Naglaa M. Hassan (Biochemical Genetics, 2018)

A new record of Neobythites multistriatus Nielsen & Quéro, 1991 (Ophidiiformes: Ophidiidae) from the Andaman Sea, North Indian Ocean - Thomy Reethas; Chippy Khader; Abhay Deshmukh; B. Kishore Kumar; Sherine Sonia Cubelio; V. N. Sanjeevan; Hashim Manjebrayakath; M. Sudhakar (Marine Biodiversity, 2018)

Taxonomic clarification and re-description of two deep-sea roughies of genus Hoplostethus from the Indian Ocean - Jacob Vinu; M. P. Rajeeshkumar; K. S. Sumod; K. M. Meera; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2017)

Occurrence of a rare gigantic sized deep-sea cod Lepidion inosimae (Günther, 1887) in the Northwestern Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2017)

Computational Approach for Securing Radiology-Diagnostic Data in Connected Health Network using High-Performance GPU-Accelerated AES - A. M. Adeshina; R. Hashim (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Erratum to: Harvesting of microalgae biomass from the phycoremediation process of greywater - Hauwa Atiku; RMSR Mohamed; AA Al-Gheethi; AA Wurochekke; Amir Hashim M. Kassim (Environmental Science and Pollution Research, 2017)

The dual roles of phycoremediation of wet market wastewater for nutrients and heavy metals removal and microalgae biomass production - N. M. Jais; R. M. S. R. Mohamed; A. A. Al-Gheethi; M. K. Amir Hashim (Clean Technologies and Environmental Policy, 2017)

An improved algorithm in unipolar weather radar calibration for rainfall estimation - A. Nikahd; M. Hashim; M. J. Nazemosadat (Innovative Infrastructure Solutions, 2016)

Harvesting of microalgae biomass from the phycoremediation process of greywater - Hauwa Atiku; RMSR Mohamed; AA Al-Gheethi; AA Wurochekke; Amir Hashim M. Kassim (Environmental Science and Pollution Research, 2016)

Three new records of rare deep-sea Anglerfishes (Lophiiformes: Ceratioidei) from the Northern Indian Ocean - Rajeeshkumar M. P.; Vinu Jacob; Sumod K. S.; Sanjeevan V. N.; Hashim M.; Sudhakar M. (Marine Biodiversity, 2016)

First record of Solitary duckbill eel, Nettastoma solitarium Castle & Smith, 1981 (Anguilliformes: Nettastomatidae) from the Andaman Sea - Sumod K. S.; Vinu J; Rajeeshkumar M. P.; S. S. Cubelio; Hashim M.; Sanjeevan V. N.; Sudhakar M. (Marine Biodiversity, 2016)

Modulation of antioxidant enzymes in Juniperus procera needles in relation to habitat environment and dieback incidence - Ibrahim M. Aref; Pervaiz R. Khan; Salim Khan; Hashim El-Atta; Abdalla I. Ahmed; Muhammad Iqbal (Trees, 2016)

First record of deep-sea gigantic pycnogonid Colossendeis colossea Wilson, 1881 from the Western Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2016)

ConnectViz: Accelerated Approach for Brain Structural Connectivity Using Delaunay Triangulation - A. M. Adeshina; R. Hashim (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Patterns of mineral lick use by Northwest Bornean orangutans (Pongo pygmaeus pygmaeus) in the Lanjak Entimau Wildlife Sanctuary, Sarawak, Malaysia - A. Ampeng; M. N. Shukor; A. R. Sahibin; W. M. R. Idris; S. Ahmad; H. Mohammad; G. P. Madeline; N. Ali; M. Bujang; I. Hashim; A. Bujang; B. M. Md-Zain (European Journal of Wildlife Research, 2016)

Immobilisation of Cu, Pb and Zn in Scrap Metal Yard Soil Using Selected Waste Materials - A. Kamari; W. P. Putra; S. N. M. Yusoff; C. F. Ishak; N. Hashim; A. Mohamed; I. M. Isa; S. A. Bakar (Bulletin of Environmental Contamination and Toxicology, 2015)

Cytotoxic ceramides from the Red Sea sponge Spheciospongia vagabunda - Enas Elsayed Eltamany; Amany K. Ibrahim; Mohamed M. Radwan; Mahmoud A. ElSohly; Hashim A. Hassanean; Safwat A. Ahmed (Medicinal Chemistry Research, 2015)

Effect of metabolites isolated from Cuscuta pedicellata on high fat diet-fed rats - Salwa H. Zekry; Dina M. Abo-elmatty; Rawia A. Zayed; Mohamed M. Radwan; Mahmoud A. ElSohly; Hashim A. Hassanean; Safwat A. Ahmed (Medicinal Chemistry Research, 2015)

Assessment of Landsat 7 Scan Line Corrector-off data gap-filling methods for seagrass distribution mapping - M.S. Hossain; J.S. Bujang; M.H. Zakaria; M. Hashim (International Journal of Remote Sensing, 2015)

ConnectViz: Accelerated approach for brain structural connectivity using Delaunay triangulation - A. M. Adeshina; R. Hashim (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Arsenic removal from soil with high iron content using a natural surfactant and phosphate - S. Mukhopadhyay; M. A. Hashim; M. Allen; B. Sen Gupta (International Journal of Environmental Science and Technology, 2015)

The application of remote sensing to seagrass ecosystems: an overview and future research prospects - M.S. Hossain; J.S. Bujang; M.H. Zakaria; M. Hashim (International Journal of Remote Sensing, 2015)

CAHECA: Computer Aided Hepatocellular Carcinoma therapy planning - A. M. Adeshina; R. Hashim; N. E. A. Khalid (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Stability and performance enhancements of Electrokinetic-Fenton soil remediation - Y. S. Ng; B. Sen Gupta; M. A. Hashim (Reviews in Environmental Science and Bio/Technology, 2014)

New fatty acids from the Red Sea sponge Mycale euplectellioides - Gamal A. Mohamed; Ali E.E. Abd-Elrazek; Hashim A. Hassanean; Abdulrahman M. Alahdal; Ameen Almohammadi; Diaa T.A. Youssef (Natural Product Research, 2014)

Case–control study on risk factors associated with Brucella Melitensis in goat farms in Peninsular Malaysia - Pwaveno Huladeino Bamaiyi; Latiffah Hassan; Siti Khairani-Bejo; Mohamed ZainalAbidin; Mohamed Ramlan; Nookaya Krishnan; Azri Adzhar; Nahariah Abdullah; Nik Husin M. Hamidah; Mokthar M. Norsuhanna; Siti N. Hashim (Tropical Animal Health and Production, 2014)

Learning to read upside-down: a study of perceptual expertise and its acquisition - Elsa Ahlén; Charlotte S. Hills; Hashim M. Hanif; Cristina Rubino; Jason J. S. Barton (Experimental Brain Research, 2014)

Simultaneous determination of metformin, captopril, lisinopril, and enalapril by RP-HPLC: its applications in dosage formulations and in human serum - M. Saeed Arayne; Najma Sultana; M. Hashim Zuberi; Farhan Ahmed Siddiqui; Urooj Haroon (Medicinal Chemistry Research, 2013)

Catch composition, reproductive biology and diet of the bramble shark Echinorhinus brucus (Squaliformes: Echinorhinidae) from the south‐eastern Arabian Sea - K. V. Akhilesh; K. K. Bineesh; W. T. White; C. P. R. Shanis; M. Hashim; U. Ganga; N. G. K. Pillai (Journal of Fish Biology, 2013)
Fishery and biological data are presented for the poorly known bramble shark Echinorhinus brucus (Squaliformes: Echinorhinidae), from the deep waters of the south‐eastern Arabian Sea. A total of 5318 individuals from by‐catch landings of deep‐water bottom set longlines, gillnets and shrimp trawl fisheries operating at depths of 200–1200 m were recorded between January 2008 and December 2011 at the Kochi Fisheries Harbour (Kerala). A total of 431 individuals, from 46 to 318 cm total length ( L T ) and 0·8 to 132 kg total mass ( M T ), were examined to determine biological data for this species. The L T at which 50% were mature ( L T 50) for females and males was estimated at 189 and 187 cm L T . Litter size ranged from 10 to 36 and size at birth was between 42 and 46 cm L T . Dietary analysis of stomach contents revealed E. brucus feeds on a variety of prey including crustaceans (69% index of relative importance, I RI ), teleosts (25·8% I RI ), cephalopods (1·7% I RI ) and elasmobranchs (0·7% I RI ). This study provides the first detailed biological data for this species and also highlights the extent of the by‐catch fishery for this species in Indian waters.

Anti-H5N1 virus new diglyceride ester from the Red Sea grass Thallasodendron ciliatum - Amany K. Ibrahim; Ahmed I. Youssef; Abdel Satar Arafa; Reda Foad; Mohamed M. Radwan; Samir Ross; Hashim A. Hassanean; Safwat A. Ahmed (Natural Product Research, 2013)

Flash flood inundation map preparation for wadis in arid regions - Zekai Şen; Hussam A. Khiyami; Saad G. Al-Harthy; Faisal A. Al-Ammawi; Ali B. Al-Balkhi; Mohammed I. Al-Zahrani; Hashim M. Al-Hawsawy (Arabian Journal of Geosciences, 2013)

Drought-induced adaptive changes in the seedling anatomy of Acacia ehrenbergiana and Acacia tortilis subsp. raddiana - Ibrahim M. Aref; Abdallah I. Ahmed; Pervaiz R. Khan; Hashim A. El-Atta; Muhammad Iqbal (Trees, 2013)

Titania-supported silver-based bimetallic nanoparticles as photocatalysts - M. A. Barakat; R. I. Al-Hutailah; M. H. Hashim; E. Qayyum; J. N. Kuhn (Environmental Science and Pollution Research, 2013)

Linkage analysis of a large African family segregating stuttering suggests polygenic inheritance - M. Hashim Raza; E. Michael Gertz; Jennifer Mundorff; Joseph Lukong; Judith Kuster; Alejandro A. Schäffer; Dennis Drayna (Human Genetics, 2013)

Multimodal 3-D reconstruction of human anatomical structures using surlens visualization system - A. M. Adeshina; R. Hashim; N. E. A. Khalid; S. Z. Z. Abidin (Interdisciplinary Sciences: Computational Life Sciences, 2013)

Simultaneous determination of glipizide and glimepride by Rp-Hplc in dosage formulations and in human serum - Najma Sultana; M. Saeed Arayne; Saeeda Nadir Ali; M. Hashim Zuberi (Medicinal Chemistry Research, 2012)

Locating abnormalities in brain blood vessels using parallel computing architecture - A. M. Adeshina; R. Hashim; N. E. A. Khalid; S. Z. Z. Abidin (Interdisciplinary Sciences: Computational Life Sciences, 2012)

Optimization of quantitative analysis of buclizine hydrochloride using UV spectrophotometry in bulk drug and dosage formulations - Farhan Ahmed Siddiqui; Agha Zeeshan Mirza; M. Hashim Zuberi; Faiza Qureshi (Medicinal Chemistry Research, 2011)

Facile and manifest spectrophotometric methods for the determination of six quinolone antibiotics in pharmaceutical formulations using iron salts - Farhan Ahmed Siddiqui; M. Saeed Arayne; Najma Sultana; Agha Zeeshan Mirza; Faiza Qureshi; M. Hashim Zuberi (Medicinal Chemistry Research, 2010)

Small and Moderate Prandtl Number Chaotic Convection in Porous Media in the Presence of Feedback Control - M. N. Mahmud; I. Hashim (Transport in Porous Media, 2010)

Dietary stearate reduces human breast cancer metastasis burden in athymic nude mice - Lynda M. Evans; Eric C. Toline; Renee Desmond; Gene P. Siegal; Arig Ibrahim Hashim; Robert W. Hardy (Clinical & Experimental Metastasis, 2009)

Risk assessment and remediation suggestion of impacted soil by produced water associated with oil production - Hashim R. Abdol Hamid; Walid M. S. Kassim; Abdulah El Hishir; Salem A. S. El-Jawashi (Environmental Monitoring and Assessment, 2008)

Two new flavonoids from Centella asiatica (Linn.) - Ravi Subban; A. Veerakumar; R. Manimaran; K. M. Hashim; Indira Balachandran (Journal of Natural Medicines, 2008)

Somatic embryogenesis in wild relatives of cotton (Gossypium Spp.) - Abdul Qayyum Rao; S. Sarfraz Hussain; M. Saqib Shahzad; S. Yassir Abbas Bokhari; M. Hashim Raza; Allah Rakha; A. Majeed; A. Ali Shahid; Zafar Saleem; Tayyab Husnain; S. Riazuddin (Journal of Zhejiang University-SCIENCE B, 2006)

The South Africa Stress and Health Study: Rationale and Design - David R. Williams; Allen Herman; Ronald C. Kessler; John Sonnega; Soraya Seedat; Dan J. Stein; Hashim Moomal; Colwick M. Wilson (Metabolic Brain Disease, 2004)

An alkalophilic thermostable lipase produced by a new isolate of Bacillus alcalophilus - Essam H. Ghanem; Hashim A. Al-Sayed; Kareema M. Saleh (World Journal of Microbiology and Biotechnology, 2000)